2019
DOI: 10.1021/acs.jpclett.9b00639
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Molecular Systems are Positively Cooperative, but Charged Molecular Systems are Negatively Cooperative

Abstract: Molecular systems bound together through noncovalent interactions are ubiquitous in nature, many of which are involved in essential life processes, yet little is known about the principles governing their structure, stability, and function. Cooperativity as one of the intrinsic properties in these systems plays a key role. In this work, on the basis of our recent quantification scheme of the cooperativity effect, we present a general pattern to identify which systems are positively cooperative and which are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 53 publications
(68 reference statements)
1
67
0
Order By: Relevance
“…Using simple atomic and molecular clusters as examples (Scheme ), we showed that both positive and negative cooperativity are possible. We found that cooperativity in charged molecular systems is negative, whereas that in homogeneous molecular systems is positive (Figure ) . We additionally unveiled that negative cooperativity is dictated by the electrostatic interaction but positive cooperativity is governed by the exchange‐correlation interaction and steric effect.…”
Section: Recent Applicationsmentioning
confidence: 70%
See 3 more Smart Citations
“…Using simple atomic and molecular clusters as examples (Scheme ), we showed that both positive and negative cooperativity are possible. We found that cooperativity in charged molecular systems is negative, whereas that in homogeneous molecular systems is positive (Figure ) . We additionally unveiled that negative cooperativity is dictated by the electrostatic interaction but positive cooperativity is governed by the exchange‐correlation interaction and steric effect.…”
Section: Recent Applicationsmentioning
confidence: 70%
“…For systems with NCI, which are characterized by the cooperativity effect due to the competition and compromise among two or more interactions, we recently quantify the cooperativity effect with the interaction energy and analyzed the nature and origin of the cooperativity effect with ITA and other density‐based quantities . Using simple atomic and molecular clusters as examples (Scheme ), we showed that both positive and negative cooperativity are possible.…”
Section: Recent Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The term “cooperativity” is widely used in chemistry to indicate the non‐additivity of the effects of generally similar or identical groups or molecules, interacting so as to produce an overall variation in a phenomenon or property which is greater than the sum of their individual effects 1–5 . In the context of hydrogen bonding, this implies that bond strengths should be mutually enhanced, that is, that the strengths of two interacting bonds should be higher than those of the isolated bonds 6 .…”
Section: Introductionmentioning
confidence: 99%